Small G protein signalling modulator 2 (SGSM2) is involved in oestrogen receptor-positive breast cancer metastasis through enhancement of migratory cell adhesion via interaction with E-cadherin. Issue 1 (1st January 2019) - Lin, Juo-Han; Lee, Wen-Jui; Wu, Han-Chung; Wu, Chih-Hsiung; Chen, Li-Ching; Huang, Chi-Cheng; Chang, Hang-Lung; Cheng, Tzu-Chun; Chang, Hui-Wen; Ho, Chi-Tang; Tu, Shih-Hsin; Ho, Yuan-Soon
ABSTRACT: The function of small G protein signalling modulators (SGSM1/2/3) in cancer remains unknown. Our findings demonstrated that SGSM2 is a plasma membrane protein that strongly interacted with E-cadherin/β-catenin. SGSM2 downregulation enhanced the phosphorylation of focal adhesion kinase (FAK; Y576/577), decreased the expression of epithelial markers such as E-cadherin, β-catenin, and Paxillin, and increased the expression of Snail and Twist-1, which reduced cell adhesion and promoted cancer cell migration. Oestrogen and fibronectin treatment was found to promote the colocalization of SGSM2 at the leading edge with phospho-FAK (Y397). The BioGRID database showed that SGSM2 potentially interacts with cytoskeleton remodelling and cell-cell junction proteins. These evidences suggest that SGSM2 plays a role in modulating cell adhesion and cytoskeleton dynamics during cancer migration.